2002
DOI: 10.1051/0004-6361:20020697
|View full text |Cite
|
Sign up to set email alerts
|

B1524-136: A CSS quasar with two-sided radio jets

Abstract: Abstract. We present MERLIN, global VLBI and VLBA observations of the high-luminosity, compact steepspectrum quasar B1524−136 at cm wavelengths. These observations reveal well-defined radio jets on both sides of the active nucleus, a situation which is almost unique amongst high-luminosity radio quasars. However, the radio jets on opposite sides are very dissimilar, and the overall radio structure appears highly distorted. We discuss possible implications of these observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This could possibly be caused by the jet nearly drilling through the deflecting cloud reducing the Faraday screen. A similar effect has been seen in B1524-136 (Mantovani et al 2002).…”
Section: Observations: Css Sourcessupporting
confidence: 82%
See 1 more Smart Citation
“…This could possibly be caused by the jet nearly drilling through the deflecting cloud reducing the Faraday screen. A similar effect has been seen in B1524-136 (Mantovani et al 2002).…”
Section: Observations: Css Sourcessupporting
confidence: 82%
“…Regions of high rotation measure have also been reported near the bends or other jet-ISM interactions in a number of CSS jets, for example 3C 119 (Flatters 1998;Nan et al 1999), 3C 216 (Lüdke et al 1998;Taylor et al 1998), and B0548+165 (Mantovani et al 2002). Figure 4 Separation of the polarised nuclear feature from the core (upper) and its Faraday rotation (lower) in the observer's frame of a polarised, moving component near the nucleus of the CSS quasar 3C 138.…”
Section: Observations: Css Sourcesmentioning
confidence: 92%
“…Taylor (2000) noted that in coredominated QSOs the highest RMs are to be found in the inner 20 pc of the nuclear region. In both the quasars reported by Mantovani et al (2002) large RMs are also found in the jets at distances of a few 100 pc where the radio-emitting material is interacting with dense gas. In 3C 43, the core is unpolarised and the high RM is also likely to be from the bent jet.…”
Section: Resultsmentioning
confidence: 85%
“…Results for the first two CSS quasars observed in this project, 0548+165 and 1524−136, are available in Mantovani et al (2002). Data analysis of VLBA observations is still in progress for the sources 3C 119, 3C 147, 3C 318, 3C 343, and 4C 24.61.…”
Section: Introductionmentioning
confidence: 99%
“…VLA observations at 5 GHz show B1524−136 to be slightly extended, while at 15 GHz it is resolved into a double source (Mantovani et al 1994). Observations with the VLBA show the northern region to have a very high rotation measure in the range of −3000 to −10000 rad m −2 in the rest frame of the source (Mantovani et al 2002).…”
Section: Introductionmentioning
confidence: 94%